AI-centric smart city ecosystem : technologies, design and implementation - Khang, Alex; Rani, Sita; Sivaraman, Arun Kumar (Boca Raton : CRC Press, 2023)
"Over the next few years, smart city technologies will be rolled out and the IoT devices and AI-Centric systems will provide even more far-reaching connectivity. This book presents various concepts in the design and development of a smart city as well as methodologies and solutions involved in designing contemporary infrastructure for building smart cities around the world. The book will focus mainly on six areas of smart city infrastructure that are smart city entities, IoT-based solutions, AI-centric control systems, Smart Systems, Cyber Security Mechanisms, Data Science and Cloud Computing for the deployment of the smart ecosystem. AI-Centric Smart City Ecosystem: Technologies, Design, and Implementation will discuss the role of AI-centric innovative systems and beyond intelligent solutions in the smart city framework. Readers will discover how to apply design principles and technologies for operating intelligent cities and develop an understanding of how to integrate AI-based control systems to make systems smarter. The book will present various concepts in the design and development of the smart cities as well as methodologies and solutions involved in designing modern infrastructure, also you can discover how to develop applications and connect the IoT devices for collecting and mining real-time data and uncover the challenges and techniques for improving the automatic operation in the smart city by using the high-tech solutions. This book is intended to serve the needs of industry, engineers, professionals, researchers, master and doctoral students studying emerging technologies in smart city ecosystems"--
Smart city ecosystem : concept, sustainability, design principles and technologies / Sita Rani, Pankaj Bhambri, Aman Kataria, Alex Khang PH -- Cyber-physical-social system and incident management / Alex Khang PH, Vladimir Hahanov, Gardashova Latafat Abbas, Vugar Abdullayev Hajimahmud -- Smart city models using applications of the internet of things / M.P. Karthikeyan, N.Muthumani, Ananthi Sadhasivam, Leelavathy Vellingiri -- Smart city framework : technologies and applications / Prerna Sharma, Kumar Guarve, Sumeet Gupta, Kashish Wilson -- Database privacy and security in cryptography for smart city / Smita Ghosh -- An approach security to manage smart city's image data on cloud / Manish Kumar Mukhija, Satish Kumar Alaria, Pooja Singh -- The role of nano electronics devices in smart city ecosystem / Mukesh Patidar, Namit Gupta, Ankit Jain, Nilesh Patidar -- Autonomous robots for smart city : closer to augmented humanity / Abdullayev Vugar Hajimahmud, Alex Khang PH, Vladimir Hahanov, Eugenia Litvinova, Svetlana Chumachenko, Abuzarova Vusala Alyar -- Drone networks and monitoring system in smart cities / B. Prabu, R. Malathy, MNA. Gulshan Taj, N. Madhan -- Smart vehicle parking management with iot technology / S.K. Chaya Devi, Sai Krishna Reddy Koppula -- The IoT-based estimation of human heart state for the smart health care system / Vikas Verma, Abhishek Vishnoi -- Application of robotic process automation in loan sanctioning process for smart bank office / R.K Tailor, Nidhi Sharma -- Epidemic awareness spreading in smart cities using artificial neural network / R. Dhanalakshmi, N. Vijayaraghavan, Arun Kumar Sivaraman, Sita Rani -- Smart libraries as promoters of development in the smart city context : a smart library infrastructure model proposal / Humberto Martínez-Camacho -- AI-based smart education system for smart city using improved self-adaptive frog leaping algorithm / Ahmed Muayad Younus, Mohanad S.S. Abumandil Veer P. Gangwar, Shashi Kant Gupta -- Smart healthcare solutions for smart cities / Meetali Chauhan -- Advanced technologies and data management in the smart healthcare system / Alex Khang PH, Nazila Ali Ragimova, Vugar Abdullayev Hajimahmud, Abuzarova Vusala Alyar -- The key assistant of smart city -- sensors and tools / Alex Khang PH, Vladimir Hahanov, Eugenia Litvinova, Svetlana Chumachenko, Vugar Abdullayev Hajimahmud, Abuzarova Vusala Alyar.
OCLC-licensed vendor bibliographic record.
Keywords: Smart cities; Artificial intelligence